THE RESISTANCE OF WOOD PLASTIC COMPOSITE TO THE DRY-WOOD TERMITE Cryptotermes cynocephalus Light. AND THE SUBTERRANEAN TERMITE Coptotermes curvignathus Holmgren INFESTATION - Jasni Jasni; Nurwati Hadjib; Barly Barly; Yusuf Sudo Hadi; Y. Afidudin (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2004)
Wood plastic composites (WPC) were made by impregnating monomer and vinyl acetate monomer with addition of terbutyl peroxide catalyst. This laboratory scale experiment aimed at looking into the durability of WPC polymerized at varying mixture ratios between styrene and vinyl acetate monomers, compared to the natural durability of the corresponding wood treated with impralit CKB. In this regard, wood samples were dried until 10 % moisture content, and then they were put in the tank under 20 mm Hg vacuum was being released. Styrene monomer with vinyl acetate addition was flown to the tank, and the wood samples were immersed in the monomer for 24 hours. Furthermore, the wood samples were taken out, and wrapped with aluminum foil, and then were put in the oven for 24 hours at 60° C. The wraps were opened, and the samples were conditioned. The samples were tested to dry wood termite (Cryptotermes cynocephalus Light.), and the Subterranean termite (Coptotermes curvignathus Holmgren.). Investigated factors were (i) wood species consisting of sengon, pine, and rubber wood, and (ii) ratio of styrene to vinyl acetate. i.e. 90/10; 80/20; 70/30; and 60/40. For comparison, each wood samples treated with Impralit CKB 3% and untreated (unpolymerized) wood samples (a control) were also prepared. The results showed that polymer loadings in the sengon, pine and rubber wood were 118 %, 72 % and 44% respectively. Increasing of vinyl acetate to styrene tended to decrease polymer loading, the addition of 10% gave 96% polymer loading, 20% gave 108%, 30% gave 71 %, and 30% gave 38 % respectively. It appeared that treatment of styrene with low vinyl acetate additions (60:40) had resulted in consecutively 95.67% and 97.75 % mortality of the dry wood termite and sub subterranean termite. This implied that the treatment might increase the wood resistance to the wood destroying insect.